Policy Communication and Stakeholder Resistance: A Comparative Reception Analysis of Malioboro Street Vendor Relocation in Yogyakarta - Kasih, Anggun (Kanal: Jurnal Ilmu Komunikasi, 2026)
Relocation of street vendors (PKL) in Malioboro Yogyakarta to Teras Malioboro 2 has triggered social resistance and policy communication challenges. Despite aiming to transform the area into a world-class cultural heritage destination, the relocation faced critical issues of information clarity, public participation, and justice perceptions. This study examines public communication strategies by local government and evaluates how relocation policy messages were received and interpreted by two key groups: vendors and visitors. Using a critical-constructivist qualitative approach, in-depth interviews were conducted with 13 informants (5 vendors, 3 vendor associations, 5 visitors) at Teras Malioboro. Thematic analysis revealed three core findings: (1) Information asymmetry caused confusion and distrust due to inconsistent policies and lack of transparency in stall allocation; (2) Minimal two-way dialogue intensified resistance, with vendors excluded from decision-making; (3) Divergent decoding positions (Hall’s theory) emerged: dominant acceptance (optimistic vendors), negotiated understanding (critical visitors), and opposition (marginalized vendors). Policy Implementation Theory (Pressman & Wildavsky) contextualizes communication gaps as implementation failures, while Stakeholder Theory (Freeman) highlights unbalanced interest management. Results emphasize the need for participatory, transparent, and culturally adaptive communication strategies in public space governance.